“Alchemizing Sorrow Into Deep Determination”: Emotional Reflexivity and Climate Change Engagement - Hamilton, Jo (Frontiers in Climate, 2022)
There are a range of emotions and affects related to climate change, which are experienced by different publics at different times. These include grief, fear, hope, hopelessness, guilt, anxiety and anger. When unacknowledged or unprocessed, these emotions and affects can contribute to emotional paralysis and systems of socially organized denial, which can inhibit climate change engagement at individual and collective scales. Emotional reflexivity describes an awareness of the ways that people engage with and feel about issues, how this influences the actions they take and their perceptions of possible change. Emotional reflexivity could be developed through approaches that incorporate psychological and social engagements with climate change. In this paper I highlight knowledge gaps concerning how practices of emotional reflexivity relate to people becoming and remaining engaged with climate change and how emotions move and change through the questions of: what is the role of emotional reflexivity in engaging with climate change? and how do emotions associated with climate move and change?, responding to the gap, and associated question of what approaches could help develop emotional reflexivity around climate change?, in this paper I present a summary of research conducted in the UK during 2018–2020 with participants of two such approaches: the “Work That Reconnects”/“Active Hope” and the “Carbon Literacy Project”. I demonstrate how emotional reflexivity was developed through: 1. Awareness and acknowledgment of emotions, which helped to facilitate feedback between the dimensions of engagement and contributed to becoming engaged with climate change, and 2. Expression and movement of emotions, which enabled a changed relationship to, or transformation of emotions, which contributed to a more balanced and sustained engagement. Key findings included the relationship between ongoing practices of emotional reflexivity and engaging and sustaining engagement with climate change, and that some approaches helped to cultivate an emotional reflexivity which contributed to a “deep determination” and ongoing resource to act for environmental and social justice, and to live the future worth fighting for in the present. However, without ongoing practices, my research evidenced forms of defensive coping, ambivalence and vacillation, which impeded active engagement over time. These findings attest to the importance of attention to the dynamics and movement of emotions and affects relating to climate change.